The Effect of Power on Inductively Coupled Plasma Parameters - Hafh Marza, Hawraa; Thamir H. Khalaf (Iraqi Journal of Physics, 2022)
In this work, we studied the effect of power variation ​​on inductively coupled plasma parameters using numerical simulation. Different values ​​were used for input power (750 W-1500 W), gas temperature 300K, gas pressure (0.02torr),         5 tourns of the copper coil and the plasma was produced at radio frequency (RF) 13.56 MHZ on the coil above the quartz chamber. For the previous purpose, a computer simulation in two dimensions axisymmetric, based on finite element method, was implemented for argon plasma. Based on the results we were able to obtain plasma with a higher density, which was represented by obtaining the plasma parameters (electron density, electric potential, total power, number density of argon ions, electron temperature, number density of excited argon atoms) where the high density in the generated plasma provides a greater degree in material processing, which increases the efficiency of the system. These results may aid in future research towards the development of more efficient optimization of plasma parameters which are (electron density, electric potential, total power, number density of argon ions, electron temperature, and number density of excited argon atoms).